Contribution of CDR3 in characterization of camelid VHH and its aflatoxin B1-binding interaction - Hina Mukhtar; Lan Ma; Qian Pang; Xiaohong Wang; Jia Wang (Food Chemistry Advances)
The single variable domain of heavy chain (VHH) antibodies, owing to their unique properties, has gained attention in immunoassays. However, compared with macromolecule antigens, in the case of small molecule haptens, such as aflatoxin B1 (AFB1), the role of the longer complementarity determining region 3 (CDR3) of VHH is still indistinct. In this study, anti-AFB1 VHH was selected from a naïve VHH library, and its CDR3 roles in VHH characteristics were further explored. Anti-AFB1 VHH-2 was selected with 6.33 × 10–5 M of KD value. Two VHH chimeras (C3-Nb28 and C3-VHH2) were constructed by interchanging the CDR3 of VHH-2 with Nb28, a previously reported anti-AFB1 VHH from immunized alpaca, and vice versa. Refolded C3-Nb28 was obtained from the inclusion body, and C3-VHH2 was purified as a soluble protein for prokaryotic expression. Computational analysis showed that the binding of VHH-2 to AFB1 is mediated by two hydrogen bonds (Thr106 and Tyr115) and two hydrophobic interactions (Trp109 and Thr114) in CDR3. In contrast, no binding pockets were available in the CDR3 in either VHH chimera, which was further confirmed by VHH ELISA. Studying the CDR3 role of VHH can elucidate its effects and affinity for small molecular weight molecules and broaden its applications.